PENGARUH VARIASI KONSENTRASI AIR JERUK NIPIS (Citrus aurantifolia) DALAM MENURUNKAN KADAR KADMIUM (Cd) PADA DAGING KERANG DARAH (Anadara granosa) - Silvia Nurvita; Nurjazuli Nurjazuli; Niki Astorina Yunita Dewanti (Jurnal Kesehatan Masyarakat (Undip), 2017)
Blood clams many consumed by Semarang’s community. Blood clams can accumulate metals in the body because its accumulated and filter feeder. Blood clams in Gayamsari’s Semarang market containing cadmium of 0.695 ppm, the level exceeds the threshold of the ILO / WHO is 0.1 ppm. This research to reduce cadmium in blood cockle using lime water. The aim of research was to determine the effect of variation lime water (Citrus aurantifolia) concentrations in reducing the levels of cadmium (Cd) in blood cockle meat (Anadara granosa). This type of research was quasi exsperiment using non randomized pretest posttest control group design. Sample population were blood clams from Gayamsari’s Semarang market. The research sample as many as 30, with 5 repetitions, 5  treatment with lime water variation of 30%, 40%, 50%, 60%, 70%. Data analysis used normality test of Shapiro – Wilk, Kruskal – Wallis and Mann – Whitney  The results showed decreased levels of cadmium from 0.695 ppm to 0.278 ppm (59.80%). Kruskal-Wallis test results demonstrate the value of p = 0.000 (p <0.05) means that there is a significant difference between the variations in the concentration of lime water with the levels of cadmium in blood clams meat. Based on the Mann – Whitney, concentrations of lime water is most effective to reduce levels of cadmium (Cd) in the blood cockle meat is 70%. Variations of lime water concentration of proved influential in reducing levels of cadmium in blood cockle meat (Anadara granosa).